2021
DOI: 10.3390/polym13121934
|View full text |Cite
|
Sign up to set email alerts
|

Application of Analytical Methods for the Comprehensive Analysis of Oleogels—A Review

Abstract: Numerous empirical studies have already been conducted on the innovative fat-replacing system defined as oleogel, creating a real urge for setting up a framework for future research, rather than conducting studies with arbitrary methods. This study re-evaluates the utility of some analyses and states some conclusions in order to eliminate the reluctance of food processors and consumers towards the utilization of oleogels as ingredients. The review presents extensively the methods applied for the characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 114 publications
0
16
0
Order By: Relevance
“…It seems that gel strength is associated with the lengths of interacting polymer and the number of hydrogen bonds. The thermoresponsive properties of oleogel make it suitable to be applied in food formulations (Pușcaș et al., 2021). The Oleogels prepared with EC (6 wt.%) showed no thermoresponsive behaviours in the range of 25–100°C.…”
Section: Resultsmentioning
confidence: 99%
“…It seems that gel strength is associated with the lengths of interacting polymer and the number of hydrogen bonds. The thermoresponsive properties of oleogel make it suitable to be applied in food formulations (Pușcaș et al., 2021). The Oleogels prepared with EC (6 wt.%) showed no thermoresponsive behaviours in the range of 25–100°C.…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that the prepared oleogels were luminous. It might be due to the presence of uniformly distributed smaller fat crystals (as seen in Figure 3 ) that reflect more incident light and become luminous [ 46 ]. It is desirable to have higher L* values in food products as it helps to improve the food color perception [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was detected that the average values of L* for all samples fall in the range of 52 to 62 ( Table 1 ), which indicates the samples are lighter in color [ 32 ]. A high L* value of food additive is desirable, as it does not interfere with the color perception of the food products [ 33 ]. The L* value obtained for the control sample was 57.45 ± 1.92.…”
Section: Resultsmentioning
confidence: 99%